Physical Disabilities and Food Access Among Limited Resource Households - Webber, Caroline B.; Sobal, Jeffery; Dollahite, Jamie S. (Disability Studies Quarterly, 2007)
Food is a basic need of all people. The degree to which people have access to food influences food choice, quality of life, health, and illness. We examined how physically impaired and disabled food shoppers from low-income households managed food provision for their families and the impact health and physical disabilities had on family food choice among those with limited resources. This qualitative study examined food access among 28 low-income rural, village, and inner city families in upstate New York selected by purposive and theoretical sampling. An unanticipated finding emerged that nearly one-half of participants, all primary grocery shoppers for their families, had a variety of health conditions and disabilities that limited food access and, in turn, healthy, affordable food. These findings suggest that physical abilities, agency, and context interact in food access.